Effect of parsley (Petroselinum crispum, Apiaceae) juice against cadmium neurotoxicity in albino mice (Mus Musculus) - Maodaa, Saleh N. (Behav Brain Funct, 2016)
BACKGROUND: Parsley was employed as an experimental probe to prevent the behavioral, biochemical and morphological changes in the brain tissue of the albino mice following chronic cadmium (Cd) administration. METHODS: Non-anesthetized adult male mice were given parsley juice (Petroselinum crispum, Apiaceae) daily by gastric intubation at doses of 10 and 20 g/kg/day. The animals were divided into six groups: Group A, mice were exposed to saline; Groups B and C, were given low and high doses of parsley juice, respectively; Group D, mice were exposed to Cd; Groups E and F, were exposed to Cd and concomitantly given low and high doses of parsley, respectively. RESULTS: Cd intoxication can cause behavioral abnormalities, biochemical and histopathological disturbances in treated mice. Parsley juice has significantly improved the Cd-associated behavioral changes, reduced the elevation of lipid peroxidation and normalized the Cd effect on reduced glutathione and peroxidase activities in the brain of treated mice. Histological data have supported these foundations whereas Cd treatment has induced neuronal degeneration, chromatolysis and pyknosis in the cerebrum, cerebellum and medulla oblongata. CONCLUSION: The low dose (5 g/kg/day) of parsley exhibited beneficial effects in reducing the deleterious changes associated with Cd treatment on the behavior, neurotransmitters level, oxidative stress and brain neurons of the Cd-treated mice.